Do Green Marketing and Perceived Value Impact Cosmetics Purchase Decisions? The Role of Brand Image as a Mediator - Salsa Jihan Fadilah; Muhartini Salim (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2025)
Purpose: This study analyzes how the cosmetic industry in Indonesia applies green marketing strategies responsibly. It also investigates how brand image mediates the relationship between green marketing, perceived value, and purchase decisions.Method: We employed a quantitative research methodology, using purposive sampling to recruit 200 participants who were familiar with Avoskin products. Data were collected through online questionnaires distributed via social media platforms. To analyze the relationships among the study variables, we applied SEM-PLS approach.Result: Our findings indicate that both green marketing and perceived value exert significant and positive influences on consumers' purchase decisions. Furthermore, we found that brand image functions as a mediating variable, enhancing the effects of green marketing and perceived value on purchasing behavior. A strong brand image amplifies the impact of environmentally friendly marketing efforts and consumers' value perceptions, thereby reinforcing their likelihood of making a purchase.Practical Implications for Economic Growth and Development: This research shows that environmentally friendly marketing strategies in the cosmetics sector can drive sustainable economic development by boosting product competitiveness, fostering green innovation, and aligning with consumer preferences.Originality/Value: The originality of our research lies in the inclusion of perceived value as a critical yet underexplored factor in the context of green marketing. By highlighting its role—alongside brand image—in shaping purchase decisions, this study offers novel insights into consumer behavior in the Indonesian cosmetics market.